2018
DOI: 10.2478/fman-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinarity in Tech Startups Development – Case Study of ‘Unistartapp’ Project

Abstract: Empirical data as well as scientific reports confirm that startups require diverse, in-house competencies in order to achieve market success. However, while technology-related competencies are usually brought to new tech ventures by their founders, there is a significant deficiency of market- and management-related competencies, which is reflected in the statistics of common startup failure reasons. In this context, a question arises: how interdisciplinarity of knowledge and competencies can be built into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Sentiment Analysis is a research methodology that analyzes the feelings of a given sample, which normally comes from digital environments such as online platforms or social networks, to find the different opinions with different methodological approaches. It has been confirmed that Sentiment Analysis can identify the feelings and therefore the opinions of product users in order to understand how these feelings and opinions affect the users' decision making [3,8]. There are different options and approaches for this technique.…”
Section: Sentiment Analysis With Social Network Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Sentiment Analysis is a research methodology that analyzes the feelings of a given sample, which normally comes from digital environments such as online platforms or social networks, to find the different opinions with different methodological approaches. It has been confirmed that Sentiment Analysis can identify the feelings and therefore the opinions of product users in order to understand how these feelings and opinions affect the users' decision making [3,8]. There are different options and approaches for this technique.…”
Section: Sentiment Analysis With Social Network Analysismentioning
confidence: 99%
“…A startup is a technology-based company that offers a new product or service using the added value of the incorporated technology. This is defined as 'innovation through technology' [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards interdisciplinary interventions between the health and technological fields, interest has been shown on numerous occasions: monitoring of the diabetic patient [37], repair and reproduction of human cells and tissues by 3D bio-printing [38] or the implementation of telemedicine as a measure to reduce infections in the COVID-19 pandemic [39]. In reference to interventions carried out in the university educational field, evidence has been found of interdisciplinary work among students in the technological and economic fields for the development of Apps [40], and between students of Biotechnology and students of Business Administration to evaluate the economic viability of innovative projects in the change of biotechnology [41]. Furthermore, the study by Pawar et al in 2017 concluded that multidisciplinary simulation education offers a positive emotional response from students and prepares them for relevant learning, dynamic thinking and a willingness to continue learning [42].…”
Section: Student Network Position and Academic Performance Results (Imentioning
confidence: 99%
“…Davila et al (2015) draw attention that the start-up enters an established market with a business model that ex-post turns out to be economically nonviable. Kopera et al (2018) explain that a source of success is rarely a technological superiority alone but rather a business model that stays behind. The business model supports the complex business endeavor, resulting in better product design and its business model configuration.…”
Section: Introductionmentioning
confidence: 99%